Quality Assurance Inputs and Goal Achievement in Public Colleges of Education in South-West, Nigeria (Kwasu International Journal of Educational Management and Leadership, 2026)
Basic schools’ teachers' competency has been put to test as a result of the quality of inputs made available within the system. Hence, this study examined quality assurance inputs and goal achievement in public Colleges of Education in South-west, Nigeria. The study adopted a descriptive research design of correlational type. Multi-stage sampling technique was used for the study; random sampling technique was used to select four states out of the six in the Zone while purposive sampling technique was used to select five out of eight public Colleges of Education in South-west, Nigeria. Proportional sampling technique was used to select 302 lecturers and 20 principal officers from selected Colleges of Education via the use of Krejcie and Morgan (1970) table for sample size determination. Two self-designed questionnaires tagged “Quality Assurance Inputs Questionnaire” (QAIQ) and (GAQ) were used to collect data for the study. Descriptive statistics of mean and standard deviation were used to answer all the three research questions; Inferential statistics of Multiple Regression was used to test the hypothesis. The findings of the study revealed that, there was significant prediction of quality assurance inputs to goal achievement in public Colleges of Education in South-west, Nigeria. Based on the findings, the study, it was recommended among others that public Colleges of Education should prioritise and invest in quality assurance inputs in order to ensure the delivery of high quality education and attainment of goals of Colleges of Education.